Application of a polymerase chain reaction test for the detection of Brucella canis from clinical samples of canines and humans (2014)
ABSTRACT: laboratory diagnosis of canine brucellosis includes serological and bacteriological tests; the blood culture is considered the gold standard, but it presents issues of sensitivity and delay in results. Therefore, the polymerase chain reaction (PCR) could be useful to detect low amounts of bacterial DNA from clinical samples and provide results within hours. Objective: to evaluate the sensitivity and specificity of PCR for the detection of Brucella canis in whole blood samples. Methods: blood samples from 499 dogs from kennels in two Colombian regions and 91 co-inhabiting humans were used. The 2-mercaptoethanol rapid slide agglutination test (2ME-RSAT) from serum and blood culture and PCR tests from whole blood were performed on all samples. Bayes theorem was used to establish the sensitivity and specificity of the PCR test compared with the other tests performed. Results: 9.9% of the evaluated co-inhabiting humans yielded positive serological results and 0% were positive by PCR or blood culture tests. 10.8% of dog samples were positive by blood culture, 19% were positive by PCR and 13% were positive by 2ME-RSAT. 7% of the samples were positive by all tests. Compared with blood culture, PCR had a sensitivity of 92.6% and a specificity of 90% for canine samples. Compared with 2ME-RSAT, it had a sensitivity of 77.4% and a specificity of 89.2%. When PCR and 2ME-RSAT results were compared with blood culture, a higher number of positive samples were retrieved than when results of only individual tests were applied. Conclusions: PCR is useful to detect B. canis in clinical samples; however, it is preferable to include the 2ME-RSAT test, as this improves the accuracy of the diagnosis. The PCR results are obtained within 24 to 48 hours and do not require the presence of whole bacterial cells to detect DNA.